2006
DOI: 10.2166/wst.2006.236
|View full text |Cite
|
Sign up to set email alerts
|

Thermal pretreatment of the solid fraction of manure: impact on the biogas reactor performance and microbial community

Abstract: Application of thermal treatment at 100-140 degrees C as a pretreatment method prior to anaerobic digestion of a mixture of cattle and swine manure was investigated. In a batch test, biogasification of manure with thermally pretreated solid fraction proceeded faster and resulted in the increase of methane yield. The performances of two thermophilic continuously stirred tank reactors (CSTR) treating manure with solid fraction pretreated for 40 minutes at 140 degrees C and non-treated manure were compared. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…T-RFLP profiles (Mladenovska et al 2006) and DGGE band patterns (Bodelier et al 2005;Connaughton et al 2006) were found to reflect the change in the microbial population. In the present study, the microbial community dynamics in a CSTR during anaerobic co-digestion of cow manure and grass silage were investigated by 16S rRNA gene-based T-RFLP and DGGE analyses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…T-RFLP profiles (Mladenovska et al 2006) and DGGE band patterns (Bodelier et al 2005;Connaughton et al 2006) were found to reflect the change in the microbial population. In the present study, the microbial community dynamics in a CSTR during anaerobic co-digestion of cow manure and grass silage were investigated by 16S rRNA gene-based T-RFLP and DGGE analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Both methods have several advantages over other fingerprinting methods, since they have high sample throughput, and enable the resolution of a complete target community. Very recently, DGGE and T-RFLP profiling have been used in exploring microbial community structure in the anaerobic digestion of industrial wastes (Connaughton et al 2006) and manure (Mladenovska et al 2006), and codigestion of food waste and biosolids (McMahon et al 2001). It is anticipated that knowledge on both the structure of microbial communities and the relations between microbial community structure and digester performance during anaerobic co-digestion of crops and manure would also be obtained by DGGE and T-RFLP profiling.…”
Section: Introductionmentioning
confidence: 99%
“…In a relatively recent investigation, laboratoryscale CSTRs were operated with manure, at 55°C, a HRT of 18 days, and an organic loading rate (OLR) of 2.5 g VS/l/day (Mladenovska et al 2005).…”
Section: The Effect Of Reactor Configurationmentioning
confidence: 99%
“…[6]. Thermal pretreatment of the solid fraction of manure was reported to improve the yield by 9%-24% [7]. Extrusion applied on straw and the solid fraction of manure resulted in 70% and 27% increases, respectively [8].…”
Section: Introductionmentioning
confidence: 99%